1998
DOI: 10.1091/mbc.9.6.1479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age on the Posttranscriptional Regulation of CCAAT/Enhancer Binding Protein α and CCAAT/Enhancer Binding Protein β Isoform Synthesis in Control and LPS-Treated Livers

Abstract: The CCAAT/enhancer binding protein alpha (C/EBPalpha) and CCAAT/enhancer binding protein beta (C/EBPbeta) mRNAs are templates for the differential translation of several isoforms. Immunoblotting detects C/EBPalphas with molecular masses of 42, 38, 30, and 20 kDa and C/EBPbetas of 35, 20, and approximately 8.5 kDa. The DNA-binding activities and pool levels of p42(C/EBPalpha) and p30(C/EBPalpha) in control nuclear extracts decrease significantly whereas the binding activity and protein levels of the 20-kDa isof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
72
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 52 publications
10
72
1
Order By: Relevance
“…The increased response with age to various inducers of stress and inflammation usually has been attributed to abnormal regulation of the levels of systemic mediators. Our findings, however, along with those of other studies, [6][7][8] implicate the cell signaling machinery in the phenomenon. We show that IL-1␤ evokes a more potent JNK response in hepatocytes isolated from aged rats than in hepatocytes isolated from young rats.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The increased response with age to various inducers of stress and inflammation usually has been attributed to abnormal regulation of the levels of systemic mediators. Our findings, however, along with those of other studies, [6][7][8] implicate the cell signaling machinery in the phenomenon. We show that IL-1␤ evokes a more potent JNK response in hepatocytes isolated from aged rats than in hepatocytes isolated from young rats.…”
Section: Discussionsupporting
confidence: 83%
“…5 Aging, however, also affects the cellular response to a variety of agents, including lipopolysaccharide (LPS) and tumor necrosis factor alpha, as well as the response to pharmacological inducers of oxidative stress. [6][7][8] Peritoneal macrophages, hepatocytes, and glial cells isolated from aged animals exhibit more severe and prolonged responses to inflammatory challenges compared with cells originating from young animals. [6][7][8][9] This hyperresponsiveness is manifested in altered activation patterns of cyclooxygenase-2, c-jun N-terminal kinase (JNK), nuclear factor kappa-B, CCAAT/enhancer binding protein alpha, and CCAAT/enhancer binding protein beta.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that p38, p34, p20, and variable amounts of p14-C/EBP␤ are present in liver extracts (17,18,28,30). These C/EBP␤ isoforms were presumed to arise from alternative translational start sites from within the coding sequence (17).…”
Section: The Appearance Of P20-c/ebp␤ In Cell Extractsmentioning
confidence: 98%
“…1A, lane 7). Previous reports have speculated that translation initiating at Met-207 generates a 14-kDa isoform of C/EBP␤ (18,28). Therefore, we constructed a vector that encodes the C-terminal polypeptide initiating at Met-207 (29) and expressed this protein in HepG2 cells.…”
Section: The Appearance Of P20-c/ebp␤ In Cell Extractsmentioning
confidence: 99%